Analisis Peran Sistem Informasi Manajemen Rumah Sakit (SIMRS) Dalam Meminimalisir Human Error Pada Pengelolaan Data di Rumah Sakit: Studi Literatur - Stella Putriseptiyani Septeragil; Kharisma Yulia Fauzi; Alfi Nazilatun Muntafi’ah; Gustin Setyaningsih (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Hospital Management Information Systems (HMIS) are information technology-based systems designed to integrate various hospital service, administrative, and data management processes. The implementation of HMIS has become an essential strategy for improving healthcare service quality while minimizing human error in hospital data management. This study aims to analyze the role of HMIS in minimizing human error through a literature review. Findings indicate that HMIS significantly reduces data entry errors, information duplication, and reporting delays. HOT-Fit evaluation at RSU Mitra Sejati Medan and RSUD Bahteramas shows that system use and user satisfaction are key factors significantly influencing net benefit. A study at RS Husada Jakarta statistically proved that nurses who do not use HMIS effectively are 8 times more likely to perform poorly. Various challenges including infrastructure limitations, staff resistance, and insufficient IT personnel were identified. The success of HMIS implementation is influenced not only by technological factors but also by organizational factors including management support, organizational culture, staff competency, continuous training, and standard operating procedures. Strong organizational commitment is required to maximize HMIS potential in reducing human error.